2004
DOI: 10.1002/biof.5520220126
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐obesity actions of green tea: Possible involvements in modulation of the glucose uptake system and suppression of the adipogenesis‐related transcription factors

Abstract: To investigate mechanisms of the anti-obesity actions of green tea in vivo, rats were given green tea instead of drinking water for 3 weeks. It was confirmed that green tea reduced adipose tissue weight without any change in body weight, other tissue weights, and food and water intakes. Green tea also significantly reduced the plasma levels of cholesterols and free fatty acids. Certain catechins existed in the plasma at 0.24 microM under our experimental conditions, though most of them existed as conjugated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
84
1
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 10 publications
6
84
1
5
Order By: Relevance
“…Food intake by rats has been shown to be reduced by the treatment of EGCG and is proposed to contribute to the weight-loss effect of EGCG [22]. In contrast, there are also reports claiming that supplementation with green tea or GTCs does not significantly affect food consumption [4,23]. These discrepancies may be caused by different supplementation methods and concentrations of GTCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Food intake by rats has been shown to be reduced by the treatment of EGCG and is proposed to contribute to the weight-loss effect of EGCG [22]. In contrast, there are also reports claiming that supplementation with green tea or GTCs does not significantly affect food consumption [4,23]. These discrepancies may be caused by different supplementation methods and concentrations of GTCs.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies and experimental data show that drinking green tea or administration of its components, green tea catechins (GTCs), is associated with a lower risk of obesity [3][4][5][6][7][8][9][10]. Moreover, GTCs are involved in modulating fat metabolism [3,5,6,8,[11][12][13], but the mechanisms are not clear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that certain phenolic compounds present in antioxidant-rich extracts may improve the status of at-risk individuals by ameliorating oxidative stress [18,42], improving insulin sensitivity [22], enhancing the capacity of adipocytes and skeletal muscle for glucose uptake [43,44] and by directly regulating the expression of genes related to the glycemic control [23,44,45]. It has been reported that propolis may enhance the activity of key antioxidant enzymes [46] such as superoxide dismutase, catalase and glutathione peroxidase.…”
Section: Discussionmentioning
confidence: 99%
“…Its anti-obesity effects are displayed through suppression of adipocyte differentiation and proliferation, inhibition of fat absorption from the gut and suppression of catechol-o-methyl transferase (COMT) [27]. Catechins intake decreases the risk of type 2 diabetes by increased glucose uptake into the skeletal muscles through up-regulating glucose transporter 4 (Glut 4) and by reducing translocation of Glut 4 and insulin levels in adipose tissues [57,58]. In a cell model, gamma-tocopherol treatment increases the glucose uptake by skeletal muscles under induced oxidative stress as well [59].…”
Section: Catechins and Tocopherolsmentioning
confidence: 99%